Proportion of Nicotine Dependence Among High School Students Using Fagerstrom Test for Nicotine Dependence and Correlated Factors - Alma Thahir Pulungan; Elisna Syahruddin; Feni Fitriani; Aria Kekalih (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2017)
Background: The study aims to determine the difference in the proportion of nicotine dependence among high school students using Fagerstrom Test for Nicotine Dependece set in urban and rural environment. Method: Sample size is 757 high school students from six different high school consists of class 1, 2 and 3 were selected based on stratified cluster random sampling was asked to fill out the question of smoking status and filling fagerstorm test for nicotine dependence if the respondent is smokers. Result: Amount of 167 students with smoking status and nicotine dependence measured results obtained by 28 (16.8%) persons with nicotine dependence with 8 (11.1%) people in urban areas and 20 (21.1%) people in the rural area. Factors were statistically significant to nicotine dependence is gender, the originator, type of inhale, age first smoked and number of cigarettes smoked per day. CO levels of relationship with the level of nicotine dependence shows a strong and positive patterned. Conclusion: There is a significant relationship between gender, the originator, type of inhale, age first smoked, number of cigarettes smoked per day to nicotine dependence and and level of CO exhalation to nicotine dependence. (J Respir Indo. 2017; 37(4): 307-15)